Comparative Study between Curved and Straight Pipe Heat Exchanger Using Solid Works (Journal of University of Babylon for Engineering Sciences, 2018)
This work focuses on an increase in the effectiveness for straight double pipe heat exchanger through curving the pipe through 180o. The geometry, mesh and boundary conditions are built up using solid works program. The proposed model of the curved pipe heat exchanger is subjected to different boundary conditions, according to inlet tube mass flow rate and inlet shell temperature. The simulated results confirmed that the effectiveness of the curved pipe heat exchanger is higher than straight pipe heat exchanger because the curvature of the pipe gives a longer time to exchange heat between hot and cold fluids. For fixed inlet tube mass flow rate and inlet shell temperature, the increase in the effectiveness of curved pipe is 14.86% compared to straight pipe at 357 K. The maximum effectiveness reached 13.75% at 363 K for curved heat exchanger with 0.22 kg/s inlet tube mass flow rate and fixed inlet shell temperature while it was 12.15% at 363 K for the straight pipe heat exchanger.